FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Muinatah, Wira; Sudirgo, Tony (Jurnal Paradigma Akuntansi, 2024)
This study aims to examine and obtain empirical evidence of the effect of profitability, leverage, firm size, and net working capital on cash holding in manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. The sample was selected using a purposive sampling method in accordance with predetermined criteria and obtained as many as 78 manufacturing companies. Data processing was carried out using E-views 12 software, the model chosen was the fixed effect model and analyzed using panel data regression. This study shows that profitability has a significant positive effect on cash holding, leverage has a significant negative effect on cash holding, firm size has a positive and no significant effect on cash holding, net working capital has a negative and no significant effect on cash holding.